IMPLEMENTASI TQM BERORIENTASI HARD SKILL DAN SOFT SKILL DALAM PEMBELAJARAN SEJARAH SMA DI KOTA SEMARANG (History Department, Semarang State University and Historian Society of Indonesia, 2010)
This study aims to introduce the implementation of hardskill and softskill oriented TQM in teacher’s learning of history in Senior High School in Semarang. The research model are structural fit model and significance of relationship between TQM implementation model, PDSA cycle, the model analysis of fish bone, continuous improvement , hard skills and soft skills and qualified history learning is the main target of research. Data was obtained from field studies using Likert scale questionnaire developed from the constructs and theoretical construct indicator. Analysis performed using software models SmartPLS. Implementation of PDSA cycle correlated 0879 to the implementation of fish bone analysis, correlates 0830 PDSA cycle to continuously improvement , while continuously improvement correlated 0441 and 0749 against the hard skills to soft skills. Soft skills to hard skills correlate of 0329, while the correlation of hard skills to qualified history learning is at 0673. The developed qualityfied history learning need support from the realization of the continuous (continuously improvement ) and optimal orientation of hard skills. Keywords: model, TQM, PDSA, the analysis of fish bone, hard skills, soft skills, learning the history of quality Kajian ini bertujuan mengenalkan model implementasi TQM yang berorientasi pada hardskill dan softskill dalam pembelajaran sejarah di sekolah atas Semarang pada para guru. Sebagai model penelitian, model struktural fit dan signifikasi dari korelasi antara model implementasi TQM, siklus PDSA, model analisis tulang ikan, perbaikan terus-menerus, hard skill dan soft skill, dan pembelajaran sejarah bermutu (PSB) menjadi target utama penelitian. Data didapatkan dari studi lapangan menggunakan angket skala Likert yang dikembangkan dari konstruk dan indicator konstruk teoretis. Analisis menggunakan program SmartPLS. Implementasi siklus PDSA berkorelasi 0879 terhadap implementasi model analisis tulang ikan, berkorelasi 0830 antara siklus PDSA dengan perbaikan terus-menerus, kemudian perbaikan terus menerus berkorelasi 0441 dan 0749 terhadap hard skill dan soft skill. Soft skill dengan hard skill berkorelasi 0329, sedangkan korelasi hard skill dengan pembelajaran sejarah bermutu adalah 0673. Pembelajaran sejarah bermutu yang dikembangkan membutuhkan dukungan melalui realisasi terhadap perbaikan terus menerud dan berorientasi pada hard skill. Kata kunci: Model TQM, analisis tulang ikan, hard skill, soft skill, pembelajaran sejarah bermutu